Interaction of Seeding and Nitrogen Rate on Grain Sorghum Yield in Southwest Kansas - A. J. Foster; A. Schlegel; J. D. Holman; I. A. Ciampitti; C. Thompson; Dorivar Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2017)
This study compared drilled planted sorghum at four seeding rates to planted sorghum at three different nitrogen (N) fertility levels at two locations in southwest Kansas (Garden City and Tribune). At the Garden City location, no difference was observed in yield among the drilled seeded sorghum populations greater than 27,000 seeds/a compared to the standard planted sorghum (sorghum planted at 27,000 seeds/a with a planter at 30 in.-row spacing). At Tribune, there was no difference in yield between the drilled sorghum and the standard planted sorghum (sorghum planted at 40,000 seeds/a with a planter at 30 in.-row spacing) regardless of seeding rate. Nitrogen fertilizer did not interact with seeding rate or affect yield independently at either location. The use of normalized difference vegetation index (NDVI) to assess canopy coverage suggested that planted sorghum and drilled sorghum at population greater than 40,000 seeds/a may achieve canopy coverage at a faster rate. In general, nitrogen rate and seeding rates did not affect sorghum yield. However, we did observe that drilled planted sorghum was more at risk of irregular stand emergence and required a higher seeding rate to achieve canopy closure at a rate similar to that of planted sorghum.
Keywords: sorghum; narrow row; seeding rate; nitrogen fertilizer